THE ROLE OF CONVENTIONAL AND NONCONVENTIONAL PERIODONTAL TREATMENT IN ORTHODONTIC THERAPEUTICAL DECISSION - Ionuţ Luchian; Ioana Mârţu; Irina Zetu; Silvia Mârţu (Romanian Society of Oral Rehabilitation, 2014)
Introduction Very soon after it was discovered, laser was introduced in dental medicine due to its' outstanding properties. Periodontists started to implement laser assisted therapies in the mid-eighties and since then the protocols are continuing to improve. Material and methods The current research included a batch of 20 patients who needed orthodontic treatment but also had moderate periodontal disease. The sample population was randomly divided into two groups A and B. Patients included in group A received conventional periodontal treatment and patients included in group B received supplementary laser assisted therapy. Results Patients from group B had better reduction of inflammation, less swelling, less bleeding and a higher degree of comfort both intraoperative and postoperative. Conclusions Diode laser assisted therapy proved to be a reliable option for the periodontal rehabilitation of the potential orthodontic patient.